A retrospective analysis of redo orthognathic surgery: Underlying causes, strategy, and outcome. Issue 3 (March 2023) - Choi, Bong-Kyoon; Jeon, Hong Bae; Lo, Lun-Jou; Yun, In Sik
Abstract: The aim of this study was to investigate the underlying causes of the need for redo orthognathic surgery, address surgical strategies, and evaluate postoperative outcomes. A retrospective chart review was conducted involving patients who underwent redo orthognathic surgery between January 2018 and April 2020. A total of 32 patients were included in this study. Prior to the procedures, patients' chief complaints were unfavorable facial profile, asymmetry, relapse, malocclusion, obstructive sleep apnea, and long face. To address these issues, we performed redo orthognathic surgery: this resulted in satisfactory aesthetic and functional outcomes in most cases. Considering the challenging nature of a redo orthognathic surgery, it is crucial for surgeons to accurately evaluate the patient's chief complaints and tailor individualized surgical plans to meet the patient's expectations.